P131 Fitness to fly assessment in patients with neuromuscular disease. (16th November 2010) - Humphreys, J; Agarwal, S; Cliff, I; Mathew, S; Mustfa, N
Abstract : Introduction: Patients with neuromuscular disorders (NMD) can develop ventilatory impairment due to respiratory muscle weakness but despite disability, many travel by air. The British Thoracic Society (BTS) recommends hypoxic challenge test (HCT) in those who have baseline oxygen saturation (SpO2) at sea level between 92–95%.1 However, this recommendation is based on very limited evidence. Objectives: To determine if baseline pulse oximetry at sea level provides a safe guide to predict hypoxia during flying and preclude a HCT in NMD patients. Methods: HCT performed on 12 NMD patients (11 Motor Neuron Disease and 1 Duchene's Muscular Dystrophy) attending ventilation clinic were retrospectively reviewed. HCT was performed to assess their fitness to fly irrespective of their baseline SpO2 . A fall in PaO2 <6.6 kPa was considered positive, PaO2 between 6.6 and 7.4 kPa was considered borderline and >7.4 kPa was considered negative.1 Spirometry and sniff nasal inspiratory pressure (SNIP) were also recorded. Results: There were nine male and three female patients, age range 27–72 years (median 63 years). Four patients were positive for HCT and two had borderline results. Only two patients among this group met the criteria for HCT as per BTS recommendation. Six patients were negative for HCT and only one met the criteria for HCT. There was no difference in median FEV1 (1.85 vs 2.04 L/s) and median FVC (2.5 vs 2.41 l) between patient with positive or borderline HCT and patients with negative HCT. SNIP was lower in those who were positive or borderline than those who were negative (median 28.5 vs 43 cmH2 O). Conclusions: Patients with NMD and respiratory muscle weakness are prone to develop hypoxia irrespective of their baseline oxygen saturation, FEV1 and FVC. SNIP may be better at predicting the risk of hypoxia during air travel.